Thank You, Amelia Bedelia - Peggy Parish (New South Wales, Australia HarperCollins Publishers (Australia) Pty Ltd, 1995)
A newly illustrated edition of an Amelia Bedelia classic, now in an I Can Read format, features the hilariously literal-minded housekeeper as she strips the sheets, pares the vegetables, and makes a jelly roll. Simultaneous.
Keywords: Level Reader -- Level Reader